Genetic history of Classic Period Teotihuacan burials in Central Mexico - Aguirre Samudio, Ana J. (2017)
The ancient city of Teotihuacan was a great urban and ceremonial center, whose population grew exceptionally in the Classic Period (300 – 700 AC). Settlement patterns, culture and burials have indicated an occupation that consisted of groups of neighboring apartment compounds or barrios. We investigated the genetics of three apartment compounds in the Teotihuacan Valley through ancient DNA analysis to prove multiethnicity during the Classic Period. Amerindian mitochondrial haplogroups were identified in 10 burials from San Francisco Mazapa, 7 from San Sebastian Xolalpan, and 19 human bone tools from La Ventilla. These samples had a wide genetic diversity. Differences in genetic structures were slight but significant (p< 0.001) between the three households and 7 ancient populations from Central and Southern Mexico by FST analysis between the three barrios studied, and Xaltocan (post-conquest) was congruent with the number of migrants estimated. Tlailotlacan, another household of Teotihuacan, was different following a small interaction with Mazapa, Xolalpan and La Ventilla. Through the estimation of immigrants, the three households studied seem to have come into contact with Mayans from Xcaret in Yucatan, and this coincides with archaeological data reported. Genetic data could indicate that migration and less genetic drift may possibly lead to a more effective role in the Teotihuacan groups, suggesting that interchange with other groups was not only for commercial, service or governmental purposes, which implicated demographic integration and genetic fusion, culminating in multiethnicity during the Classic Period in Teotihuacan. Further studies can be directed to examine others households.